The genetics of tobacco use: methods, findings and policy implications. Issue 2 (1st June 2002) - Hall, W; Madden, P; Lynskey, M
Abstract : Research on the genetics of smoking has increased our understanding of nicotine dependence, and it is likely to illuminate the mechanisms by which cigarette smoking adversely effects the health of smokers. Given recent advances in molecular biology, including the completion of the draft sequence of the human genome, interest has now turned to identifying gene markers that predict a heightened risk of using tobacco and developing nicotine dependence